Removal of organic pollutants in coking wastewater based on coal-based adsorbents: A pilot-scale study of static adsorption and flotation. Issue 6 (December 2021) - Gao, Qieyuan; Jin, Pengrui; Wang, Lei; Xing, Yaowen; Gui, Xiahui; Van Puyvelde, Peter; Van der Bruggen, Bart
Abstract: Coking wastewater mainly comes from coke oven gas primary cooling and production water during the coking production process, as well as steam condensate wastewater. Because of its complex and variable composition and poor biodegradability, it is considered one of the most difficult industrial wastewaters to treat. In this paper, four coal-based adsorbents were studied to treat coking wastewater before biological treatment (S1) and after biological treatment (S2). Coke powder showed better COD removal (60.3% in S1 and 74.0% in after S2) in the coking wastewater than coal adsorbents due to its well-developed pore structure that is more conducive to adsorption. With the coal adsorbents, Long flame coal had a relatively great adsorption performance (COD remove rate, 47.3% in S1 and 40.1% in S2) while CC exhibited the poorest performance (COD remove rate, 26.9% in CW-BBT and 23.4% in CW-BAT). In addition, the subsequent separation of the adsorbents by flotation was also investigated. Moreover, the flotation separation yield of coke powder in before biological treatment and after biological treatment is better than for the other three adsorbents. Therefore, coke powder has potential advantages in coking wastewater treatment. Graphical Abstract: "Monkey King and his purple gourd": Coking wastewater treatment-flotation process. (in Chinese classical novel Journey to the west) Based on the good adsorption, and flotation separation performance of coke powder, the feasibility of its industrial application was studied. Interestingly, according to the Chinese classic novel Journey to the west (Written by Wu Chengen, in 1592, in the Ming dynasty in China), the monkey king is holding the purple gourd, which has a strong adsorption capacity and could inhale monsters into it. A coal-based adsorbent is the purple gourd in monkey king's hands, and pollutants in coking wastewater are the contemporary 'monsters'. ga1 Highlights: Coal-based adsorbent were used to treat coking wastewater. Coke powder was better than long flame coal, gas fat coal and coking coal. The functional groups of coal-based adsorbents are related to the degree of deterioration. Coal-based adsorbents can be recovered by flotation separation.